An Allais paradox without mental time travel. Issue 11 (11th July 2014) - Craver, Carl F.; Cova, Florian; Green, Leonard; Myerson, Joel; Rosenbaum, R. Shayna; Kwan, Donna; Bourgeois‐Gironde, Sacha
ABSTRACT The capacity to anticipate future experiences of regret has been hypothesized to explain otherwise irrational aspects of human decision‐making, including the certainty effect (Kahneman and Tversky (1979) Econometrica 47:263–291) and the common ratio effect (Allais (1953) Econometrica 21:503–546). The anticipated regret hypothesis predicts that individuals incapable of episodically imagining their personal futures, as has been reported for people with extensive damage to medial temporal lobe structures and resulting deficits in episodic thought, should be immune to these effects. We report that K.C., who has extensive bilateral damage to his hippocampus and adjacent medial temporal lobe structures and nearly complete deficits in his ability to episodically imagine his personal future, nonetheless displays both the certainty and the common ratio effects. These results suggest that the episodic anticipation of future regret does not explain the general human tendency to display the certainty and common ratio effects. © 2014 Wiley Periodicals, Inc.